The genetic control of aposematic black pigmentation in hemimetabolous insects: insights from Oncopeltus fasciatus. Issue 5 (14th August 2014) - Liu, Jin; Lemonds, Thomas R.; Popadić, Aleksandar
SUMMARY Variations in body pigmentation, encompassing both the range of specific colors as well as the spatial arrangement of those colors, are among the most noticeable and lineage‐specific insect features. However, the genetic mechanisms responsible for generating this diversity are still limited to several model species that are primarily holometabolous insects. To address this lack of knowledge, we utilize Oncopeltus fasciatus, an aposematic hemimetabolous insect, as a new model to study insect pigmentation. First, to determine the genetic regulation of black pigment production in Oncopeltus, we perform an RNAi analysis on three core genes involved in the melanin pathway, tyrosine hydroxylase (TH), dopa decarboxylase (DDC), and laccase 2 (lac2). The black pigmentation is affected in all instances, showing that the black pigments in this species are derived from the melanin pathway. The results of the DDC RNAi are particularly informative because they reveal that it is Dopamine melanin, not DOPA melanin, which is the predominant component of black pigments in Oncopeltus. Second, we test whether pigmentation follows a two‐step model where the spatial pre‐mapping of enzymatic activity is followed by vein‐dependent transportation of melanin substances. We confirm the existence of the first step by observing that premature wings develop black pigmentation when exposed to melanin precursors. In addition, we provide evidence for the second step by showing that wing melanin patterning is disrupted when vein transportation is halted. These findings bring novel insights from a hemimetabolous species and establish a framework for subsequent studies on the mechanisms of pigment production and patterning responsible for variations in insect coloration.